2021
DOI: 10.7759/cureus.20309
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Aspirate in Spine Surgery: Case Series and Review of the Literature

Abstract: BackgroundWith the modernization of biotechnology, there has been a concerted effort to create novel biomaterials to promote arthrodesis for spine surgery. The novel use of the stem cells from bone marrow aspirate (BMA) to augment spine surgery is a burgeoning field because these cells are considered to be both osteoinductive and osteogenic. We sought to review the evidence behind the use of BMAs in spinal fusions and report the results of our own case series. MethodsPubMed and EMBASE databases were searched f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…44 BMA has been used to overcome the drawbacks of relying solely on synthetic material to promote fusion. 46 This is particularly important since synthetic materials depend on the patient's own cells to stimulate or grow new osteocytes and can be affected by the multiple comorbidities of patients. 46 The active components of BMA are mesenchymal stem cells, creating a regenerative environment.…”
Section: Most Common Types Of Graft Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…44 BMA has been used to overcome the drawbacks of relying solely on synthetic material to promote fusion. 46 This is particularly important since synthetic materials depend on the patient's own cells to stimulate or grow new osteocytes and can be affected by the multiple comorbidities of patients. 46 The active components of BMA are mesenchymal stem cells, creating a regenerative environment.…”
Section: Most Common Types Of Graft Materialsmentioning
confidence: 99%
“…46 This is particularly important since synthetic materials depend on the patient's own cells to stimulate or grow new osteocytes and can be affected by the multiple comorbidities of patients. 46 The active components of BMA are mesenchymal stem cells, creating a regenerative environment. 46 A retrospective analysis of the International Spine Study Group reported a fusion rate of 87% after multilevel ALIF at 1 year based on computed tomography (CT) grading when using mineralized collagen and BMA, 47 which is lower compared with the fusion rates of 95% or more reported in the existing literature with BMP.…”
Section: Most Common Types Of Graft Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the high cost and limited accessibility of advanced mechanical aids underscore the need for more broadly accessible and biologically focused therapies. BMA addresses these critical gaps by leveraging its regenerative potential to not only modulate inflammatory responses but also promote the regeneration of neural tissues and support functional recovery at a molecular level [16,[78][79][80]. Unlike traditional therapies, which are mostly palliative and adaptive, BMA offers a therapeutic strategy aimed at the root causes of neurodegeneration observed in SCI, providing a foundation for more definitive and sustainable recovery outcomes.…”
Section: Conventional Treatment Approachmentioning
confidence: 99%
“…This highlights the enhanced potential of PRP in facilitating the differentiation of osteoblasts and other bone-forming cells. These material advantages also include avoiding the risk of infection and fractures 12 , 13 . However, there have been only a few reports on the effects of these combinations on bone union.…”
Section: Introductionmentioning
confidence: 99%